Teachers’ Perceptions Of Main Factors Influencing Students’ Mastery Of Arabic Vocabulary - Pisal, Nadhilah Abdul; Rahim, Nadiah Abd; Ismail, Ummi Syarah Danik; Rouyan, Nurazan Mohmad; Razali, Razlina A. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Limited vocabulary mastery can interfere with the fluency of the Arabic language learning process. However, not many studies describe the causes or factors that can affect vocabulary mastery in detail and deal with this problem in the Malaysian education system. This case study explores further the main factors that can influence the mastery of Arabic vocabulary at the secondary school level. Data was collected through semi-structured interviews with six experienced teachers from four National Religious Secondary Schools (SMKA) in Kedah. Research interview data was analyzed thematically using NVivo 14 software. The study's findings show five main factors affecting vocabulary mastery: self, teacher's approach, syllabus, environment, and the Arabic language program. Based on these five factors, the self-factor is the most important and can affect how well students learn vocabulary. It includes internal factors (belief, interest, and attitude) and external factors (vocabulary use and learning strategies). Thus, teachers are suggested to focus on the students’ self-factor from internal and external aspects to help improve vocabulary mastery. It is believed that encouraging and promoting the various learning strategies, students will be more proactive and creative in enhancing their mastery of new vocabulary.